2014
DOI: 10.3758/s13428-014-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

On the number of factors to retain in exploratory factor analysis for ordered categorical data

Abstract: Conducting exploratory factor analysis (EFA) using statistical extraction methods has been recommended, but little is known about the accuracy of the decisions regarding the number of factors to retain for ordered categorical item data by considering a chi-square test, fit indices, and conventional criteria, such as eigenvalue >1 and parallel analysis. With computer-generated data, the authors examined the accuracy of decisions regarding the number of factors to retain for categorical item data, by combining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 44 publications
(67 reference statements)
4
47
0
5
Order By: Relevance
“…Bei der EFA wurde das Kaiser-Kriterium angewendet sowie X²-Differenztests für 2-bis 7-Faktoren-Lösungen durchgeführt, um die Anzahl zugrunde liegender Faktoren zu bestimmen [13,15]…”
Section: Analyseschritteunclassified
See 2 more Smart Citations
“…Bei der EFA wurde das Kaiser-Kriterium angewendet sowie X²-Differenztests für 2-bis 7-Faktoren-Lösungen durchgeführt, um die Anzahl zugrunde liegender Faktoren zu bestimmen [13,15]…”
Section: Analyseschritteunclassified
“…Aufgrund der geringen Stichprobe könnte es auch zu einer Überoder Unterschätzung der Faktorenanzahl gekommen sein [15]. Die Stichprobengröße könnte zudem für die negative Residualvarianz des Items "Tut Dinge, die ohne Sinn erscheinen" verantwortlich sein, welches aufgrund dessen aus der EFA entfernt wurde.…”
Section: Limitationen Der Studieunclassified
See 1 more Smart Citation
“…Si bien esta conclusión parcial puede estar abierta a discusión por las limitaciones propias del método 3 , sería recomendable brindar los valores de todas las cargas de cada uno de los ítems tanto del componente principal como de los componentes secundarios, y no solo las más relevantes (λ ≥ 0,40).…”
Section: Review Of the Internal Structure Of A Satisfaction Surveyunclassified
“…When the literature was reviewed, various studies regarding Parallel Analysis were identified (Buja & Eyuboglu, 1992;Cho, Li, & Bandalos, 2009;Cota et al, 1993;Dinno, 2014;Glorfeld, 1995;Green, Levy, Thompson, Lu, & Lo, 2012;Green, Redell, Thompson, & Levy, 2016;Green, Thompson, Levy, & Lo, 2015;Kaya Kalkan & Kelecioğlu, 2016;Raîche et al, 2013;Weng & Cheng, 2005;Xia, Green, Xu, & Thompson, 2019;Yang & Xia, 2015;Zwick & Velicer, 1986). It was observed that these studies mostly focused on parallel analysis processes rather than comparison of performance of factor retention methods.…”
Section: Introductionmentioning
confidence: 99%